EFEKTIFITAS POSISI ORTHOPNEA TERHADAP PENURUNAN SESAK NAFAS PADA PASIEN TB PARU - Henny Syapitri; Darwita Juniwati Barus; Flora Sijabat; Nadia Aramita (Universitas Prima Indonesia, 2023)
The incidence of tuberculosis according to the WHO Global Tuberculosis report 2016, tuberculosis occupies the second position with the highest TB burden in the world. Pulmonary TB is an inflammatory disease of the lung parenchyma caused by the bacterium Mycobacterium tuberculosis. Pulmonary TB can cause respiratory system disorders. Breathing is a condition in which air containing O2 enters the body and removes CO2 from the body as a residue of oxidation. The purpose of the study was to determine the effectiveness of the orthopnea position on the reduction of shortness of breath in pulmonary TB patients in RSUP H. Adam Malik Medan. Research design. Quasi-experimental with a two-group pretest-posttest design approach. To determine the effectiveness before and after the orthopnea position to decrease shortness of breath in pulmonary TB patients. The sample was 50 respondents, 25 for the intervention group, and 25 for the control group, using the purposive sampling technique. The study found that the mean value in the intervention group was 26,64 decreased to 21,36 and the control group was 24,80 to 24,88. Dependent test results in the intervention group obtained a value of p = 0.000 or p < 0.05 and the control group obtained a value of p = 0.161 or p> 0.05 so the intervention group had an effect and the control group had no effect. Suggestions are the effectiveness of respiratory frequency in pulmonary TB patients while the control group only measures the respiratory frequency, there is no effectiveness in pulmonary TB patients.